Bright bazaar : embracing color for make-you-smile style - Taylor, Will (Blogger) (St. Martin's Press, 2014)
"Known for his bold and refreshing take on color, Will Taylor, the founder of Bright Bazaar-- one of the world's leading interior design blogs-- shares his secrets to choosing colors that work for every room in your house. Structured around the different spaces within the home, the book breaks down the how, when, and where of using different shades and color combinations"--